Impact of corrosion on cyclic behaviors of ultra-high-strength reinforcing bars. (10th June 2019) - Hu, Menghan; Han, Qiang; Xu, Kun; Du, Xiuli
Highlights: Influence of corrosion on cyclic behaviors of UHS bars are investigated. Cyclic properties of corroded UHS bars are analyzed. Regression models are proposed for simulating these cyclic properties. Abstract: In this study, the influence of corrosion on the cyclic behaviors of ultra-high-strength (UHS, yield strength above 1000 MPa) steel bars is investigated. A total number of 63 specimens with different corrosion degrees and slenderness ratios are involved in this experiment. Some important mechanical indexes that can reflect the cyclic properties of steel bars (such as failure modes, energy dissipation and stiffness) are analyzed based on the experimental results. The influence of corrosion on these mechanical properties are quantified through regressions of experimental results. The proposed regression models can well reproduce the experimental results, which can be adopted in the modeling of cyclic behaviors of corroded UHS steel bars in future studies.